THE POLITICAL PARTIES OF THE PROVINCE OF BUENOS AIRES IN THE SECOND HALF OF THE NINETEENTH CENTURY: AN INTERPRETATION ON THE METAMORPHOSIS OF REPRESENTATION (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
Using the case of the province of Buenos Aires in the second half of the nineteenth century as a point of departure, this paper analyzes a problem often ignored by studies of the representative system and, in particular, political   parties: the process through which political parties, in addition to being considered a legitimate and necessary institution for representative government, became the main or exclusive channel of political representation. Despite its importance, the process through which political parties emerged as a central feature of the political system has often been ignored. By studying this process, this article seeks to contribute to current debates on political representation and participation.
Keywords: Political parties, Representative system, Nineteenth century, Province of Buenos Aires, Political and intellectual history